Data for bottom ash and marble powder utilization as an alternative binder for sustainable concrete construction - Mohamad Atiyeh; Ertug Aydin (Data in Brief, 2020)
In today's world where the effects of global warming are intense, alternative approaches for a sustainable concrete sector are rapidly increasing. The partial replacement of waste materials, such as bottom ash and marble powder to cement, leads to a significant reduction in carbon dioxide emissions. The expected quality of materials to be used for the concrete sector is very important in terms of building safety. New building materials and binder materials offered as an alternative are often unable to meet this requirement due to existing standards. Therefore, the existing standards should be reviewed and alternative construction materials should be provided for the sector. This dataset would be beneficial for other researchers who design sustainable concrete. Although the data presented herein deals with pure paste, the authors believe that the data can be used for mix design in the concrete construction sector to reduce the cement amount for various civil engineering projects, from low to medium strength concrete applications. The data compiled herein were obtained from the fresh and hardened properties at 7, 28 and 56 days. Physico-mechanical characterization and sulphate resistance were analyzed for laboratory produced marble paste composites. The dataset described here is the pilot study of the “High-volume marble substitution in cement-paste: towards a better sustainability” [1] and “Novel coal bottom ash waste composites for sustainable construction” [2]. Keywords: Marble powder, Cement, Paste, Composite, Sustainability, Construction, Waste